Da'i Credibility and Religious Authority Negotiation in Habib Jindan's Instagram Da'wah - Arief Ajie Pamungkas Emnoor; Agus Riyadi; Awaludin Pimay (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2026)
This study examines the construction of da'i credibility and the negotiation of religious authority in Habib Jindan's digital da'wah practices on Instagram. Grounded in Hovland's credibility theory, digital religious authority theory, and the framework of Islamic da'wah elements, this qualitative research employs content analysis of 20 selected posts from the Instagram account @alhabibjindan, which has approximately 1.3 million followers. Data were collected through non-participant observation of content, captions, and audience comments. The analysis focuses on three dimensions of credibility: trustworthiness, expertise, and attractiveness. The findings show that Habib Jindan constructs digital credibility through consistent religious messages, transparent identity representation, contextual Islamic explanations, empathetic communication styles, and symbolic religious visualizations. Trustworthiness is reflected in the consistency between messages and practices, expertise appears through the use of Qur'anic and hadith references contextualized to contemporary issues, while attractiveness is built through humanistic language, emotional engagement, and authentic visual presentation. This study also finds that the adaptation of traditional habaib authority into Instagram's platform logic creates a negotiation between religious depth and digital accessibility. Religious authority is influenced not only by sanad and scholarly recognition, but also by digital symbolic capital such as followers and engagement. Theoretically, this research contributes to digital da'wah studies through the concept of da'i credibility construction, while practically offering insights for developing adaptive and ethical da'wah strategies in social media environments.